2023
DOI: 10.3390/medicina59040714
|View full text |Cite
|
Sign up to set email alerts
|

Lung Expression of Macrophage Markers CD68 and CD163, Angiotensin Converting Enzyme 2 (ACE2), and Caspase-3 in COVID-19

Abstract: Background and Objectives: The coronavirus (SARS-CoV-2) damages all systems and organs. Yet, to a greater extent, the lungs are particularly involved, due to the formation of diffuse exudative inflammation in the form of acute respiratory distress syndrome (ARDS) with next progression to pulmonary fibrosis. SARS-associated lung damage is accompanied by the pronounced activation of mononuclear cells, damage of the alveoli and microvessels, and the development of organized pneumonia. To study the expression of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
1
0
0
Order By: Relevance
“…An important role in the development of acute lung injury and PF in COVID-19 belongs to apoptosis of alveolar epithelial cells [57,58]. It has also been shown that the high expression of caspase-3 associated with the low expression of ACE2 contributed to the severity of lung injury and PF in COVID-19 [59,60], and these findings support the present study results.…”
supporting
confidence: 90%
“…An important role in the development of acute lung injury and PF in COVID-19 belongs to apoptosis of alveolar epithelial cells [57,58]. It has also been shown that the high expression of caspase-3 associated with the low expression of ACE2 contributed to the severity of lung injury and PF in COVID-19 [59,60], and these findings support the present study results.…”
supporting
confidence: 90%